The contribution of qualitative research within the PRECISE study in sub-Saharan Africa - Marina A. S. Daniele; Melisa Martinez-Alvarez; Angela Koech Etyang; Marianne Vidler; Tatiana Salisbury; Prestige Tatenda Makanga; Peris Musitia; Meriel Flint-O'Kane; Tanya Wells Brown; Brahima Amara Diallo; Helena Boene; William Stones; et al. (BMC, 2020)
Abstract The PRECISE Network is a cohort study established to investigate hypertension, fetal growth restriction and stillbirth (described as "placental disorders") in Kenya, Mozambique and The Gambia. Several pregnancy or birth cohorts have been set up in low- and middle-income countries, focussed on maternal and child health. Qualitative research methods are sometimes used alongside quantitative data collection from these cohorts. Researchers affiliated with PRECISE are also planning to use qualitative methods, from the perspective of multiple subject areas. This paper provides an overview of the different ways in which qualitative research methods can contribute to achieving PRECISE's objectives, and discusses the combination of qualitative methods with quantitative cohort studies more generally. We present planned qualitative work in six subject areas (health systems, health geography, mental health, community engagement, the implementation of the TraCer tool, and respectful maternity care). Based on these plans, with reference to other cohort studies on maternal and child health, and in the context of the methodological literature on mixed methods approaches, we find that qualitative work may have several different functions in relation to cohort studies, including informing the quantitative data collection or interpretation. Researchers may also conduct qualitative work in pursuit of a complementary research agenda. The degree to which integration between qualitative and quantitative methods will be sought and achieved within PRECISE remains to be seen. Overall, we conclude that the synergies resulting from the combination of cohort studies with qualitative research are an asset to the field of maternal and child health.